دعوى تصحيح الأخطاء المادية أمام مجلس الدولة الجزائري - جروني, فايزة; بطينة, مليكة; جديدي, نهلة (University of Eloued جامعة الوادي, 2019)
قرّ المشرع عناية للأحكام والقرارات القضائية لما تحمله من حقوق وحريات ثابتة الحقيقة للأشخاص (أطراف الخصومة) في استقرار المجتمع وتحقيق دور سيادة القضاء فيه، فلم يكتف بوضع أحكام قانونية تحدّد بياناتها بل عززّ ذلك بإجراء في غاية الأهمية يحقّق هذه المبادئ التشريعية هو: " دعوى تصحيح الأخطاء المادية" التي ترفع ضد الأحكام والقرارات المشوبة بخطأ مادي. يهدف هذا المقال لدراسة الأحكام القانونية لدعوى تصحيح الأخطاء المادية أمام مجلس الدولة الجزائري انطلاقا من مفهومها ثم شروط ممارستها إلى غاية الفصل فيها، بناء على ما ورد في قانون الإجراءات المدنية والإدارية الساري المفعول. وقد خلصنا إلى أنه؛ رغم الأهمية البالغة لهذا الإجراء في حماية حقوق الأشخاص الواردة في الأحكام والقرارات القضائية واستقرار هذه الأخيرة وبالتالي تفعيل الوظيفة القضائية لمجلس الدولة وتجسيدها، إلا أن الإطار القانوني له تكتنفه نقاط ظل, انعكس أثرها سلبا على ممارسته كالمتعلقة بضعف هذا الإطار القانوني وإشكالية تكييفها القانوني ... وما إلى ذلك, تمّ كشفها في هذه الدراسة. Abstract: The legislator has realized the importance of judicial judgment and decisions due to the rights and freedoms they hold for parties to the dispute, and because of their role in the guarantee of the stability of society and the supremacy of justice in it. For these reasons, the legislator has not only established legal provisions that define its content, but has reinforced it by a very important procedure that fulfills these legislative principles: the "Clerical error correcting action" brought against judgment and decisions containing a clerical error. This article aims to study the legal provisions for the correction of Clerical errors before the Algerian Council of State, based on its concept and then the conditions of its commencem entand the entry of the final judgmentin accordance with the Civil and Administrative Procedures Law. We have concluded that despite the great importance of this procedure in the guarantee of protection and stability of people's rights held by the judicial judgments and decisions, and thus activating the judicial function of the State Council, its legal framework is surrounded by points whose impact has adversely affected its practice such as the weakness of this legal framework and the problem of legal adaptation… etc.
A suit to correct the material errors before the Algerian State Council
مقال
Keywords: الدعوى _ الطعن _الطلب القضائي _ الخطأ المادي - قرار التصحيح – مجلس الدولة.; Action; Appeal; Judicial .Request; Clerical Error, Correction Decision; State Council.